Effects of Lactobacillus casei on Iron Metabolism and Intestinal Microflora in Rats Exposed to Alcohol and Iron - Li, Xuelong; Liang, Hui (Turkish Journal of Gastroenterology, 2022)
Background: Higher alcohol consumption was reported in those who consumed more red meat. Both excessive alcohol and iron intake can cause damage to the liver. The purpose of this study is to investigate the effect of Lactobacillus casei strain Shirota (L. casei) on iron metabolism and intestinal microflora in rats after alcohol and iron co-exposure. Methods: Sixty male rats were randomly divided into 3 groups for 12 weeks: the control group: treated with normal saline by gavage and normal diet; the model group: treated with alcohol (8-12 mL/kg/day) by gavage and iron (1500 mg/kg) in diet; the model group supple- mented with L. casei (8 × 108 CFU/kg/day) as the L. casei group. Results: Compared with the control group, the levels of serum ferritin, hepcidin, the protein expressions of ferroportin 1 and divalent metal transporter 1 in the model group were significantly increased, while it was significantly decreased after L. casei supplement (P < .05). Compared with the control group, the amount of Lactobacillus of the model group was significantly decreased, while the amount of Bacteroides and Escherichia coli was significantly increased (P < .05). After the supplementation of L. casei, the amount of Lactobacillus increased significantly, while the amount of Bacteroides and E. coli decreased significantly (P < .05). Conclusion: L. casei could effectively improve iron metabolism and intestinal flora disorder induced by excessive alcohol and iron. The effective treatment of iron metabolism may be related to the changes of intestinal flora. Cite this article as: Li X, Liang H. Effects of Lactobacillus casei on iron metabolism and intestinal microflora in rats exposed to alcohol and iron. Turk J Gastroenterol. 2022;33(6):470-476.